Sexuality and AIDS in the Third Age - Fonseca, Suzana Carielo da (2012)
This paper aims to send a reflection that involves the relationship between age and sexuality. This theme was motivated by the realization, through epidemiological data, that Brazil assists, currently, an increasing number of new AIDS cases in the This theme was motivated by the realization, through epidemiological data, that Brazil assists, currently, an increasing number of new AIDS cases in the age group older than 60 years. If, on the one hand, this data serves to deconstruct the imagery (stigmatized) that "old does not have sex" on the other, it indicates that we must question the reasons that account for this state of affairs. Therefore, we sought to address "sexuality", "third age" and "HIV / AIDS" as concepts to then explore how their association allows you to read the reality referred to above. Finally, there is a discussion about how, in Brazil, the state and non-governmental organizations are facing the problem of health care for the elderly, more specifically, let see the social protection system available for coping with AIDS in this population segment.